Products of Orange II Biodegradation by Enterococcus faecalis ID6017 and Chryseobacterium indologenes ID6016 - VINCENTIA IRENE MEITINIARTI; ENDANG SUTARININGSIH SOETARTO; KRIS HERAWAN TIMOTIUS; EKO SUGIHARTO (Indonesian Society for microbiology, 2007)
Chryseobacterium indologenes and Enterococcus faecalis were isolated from activated sludge of textile wastewater treatment plant. These bacteria had the ability to decolorize several azo-dyes. Degradation of azo dyes was initiated by decolorization (reduction of azo bond) which occurred in anaerobic condition. In this study, we focussed on biodegradation of Orange II by pure culture of C. indologenes ID6016 and E. faecalis ID6017, and to determine the metabolite products of Orange II degradation. The degradation of Orange II by both bacteria was carried out in batch experiments using liquid medium containing 80 mg/l Orange II, under sequential static agitated incubation. During the bacterial growth under static incubation (6 h), 66.1 mg/l Orange II were decolorized by 35.54 mg/l biomass of E. faecalis ID6017, but no decolorization found with C. indologenes ID6016. Based on HPLC results, the decolorized Orange II products were identified as sulfanilic acid and amino-naphthol. These metabolites were probably used or degraded by C. indologenes ID6016 under agitated incubation.